Improving substance information in USEtox®, part 1: Discussion on data and approaches for estimating freshwater ecotoxicity effect factors. (17th August 2017) - Saouter, Erwan; Aschberger, Karin; Fantke, Peter; Hauschild, Michael Z.; Bopp, Stephanie K.; Kienzler, Aude; Paini, Alicia; Pant, Rana; Secchi, Michela; Sala, Serenella
Abstract: The scientific consensus model USEtox ® is recommended by the European Commission as the reference model to characterize life cycle chemical emissions in terms of their potential human toxicity and freshwater aquatic ecotoxicity impacts in the context of the International Reference Life Cycle Data System Handbook and the Environmental Footprint pilot phase looking at products (PEF) and organizations (OEF). Consequently, this model has been systematically used within the PEF/OEF pilot phase by 25 European Union industry sectors, which manufacture a wide variety of consumer products. This testing phase has raised some questions regarding the derivation of and the data used for the chemical‐specific freshwater ecotoxicity effect factor in USEtox. For calculating the potential freshwater aquatic ecotoxicity impacts, USEtox bases the effect factor on the chronic hazard concentration (HC50) value for a chemical calculated as the arithmetic mean of all logarithmized geometric means of species‐specific chronic median lethal (or effect) concentrations (L[E]C50). We investigated the dependency of the USEtox effect factor on the selection of ecotoxicological data source and toxicological endpoints, and we found that both influence the ecotoxicity ranking of chemicals and may hence influence the conclusions of a PEF/OEF study. We furthermore compared the average measure (HC50) with other types of ecotoxicity effect indicators, such as the lowest species EC50 or no‐observable‐effect concentration, frequently used in regulatory risk assessment, and demonstrated how they may also influence the ecotoxicity ranking of chemicals. We acknowledge that these indicators represent different aspects of a chemical's ecotoxicity potential and discuss their pros and cons for a comparative chemical assessment as performed in life cycle assessment and in particular within the PEF/OEF context. Environ Toxicol Chem 2017;36:3450–3462. © 2017 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.